PENGARUH INTENSITAS MODAL, ARUS KAS OPERASI DAN BEBAN PAJAK TANGGUHAN TERHADAP PENGHINDARAN PAJAK - Yulianawati, Mitha; Karlina , Lilis (Publika Citra Media, 2025)
This study aims to examine the effect of Capital Intensity, Operating Cash Flow, and Deferred Tax Expense on Tax Avoidance. This study uses a quantitative approach and the data used is secondary data, namely the financial statements of each sample company via the official website www.idx.com. The population in this study are consumer non-cyclical sector which are listed on the Indonesia Stock Exchange for the 2019-2023 period. Methods in determining the sample using purposive sampling. 38 samples were obtained with a five-year period so that the number obtained was 190 sample data. Testing the data using panel data regression analysis, the selected model selection test is the Fixed Effect Model with the help of eviews version 12 statistical data processing. The results of this study indicate that Capital Intensity, Operating Cash Flow, and Deferred Tax Expense simultaneously influence Tax Avoidance. Capital Intensity has an effect on Tax Avoidance. Operating Cash Flow and Deferred Tax Expense has no effect on Tax Avoidance.